Analisis Faktor-Faktor Kriminogenik Kasus Filisida di Indonesia dalam Perspektif Strain Theory - Purba, Yedija Otniel (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2025)
The phenomenon of filicide, the act of killing one’s biological, step, or adopted child, has exhibited an alarming trend in Indonesia over the past six years. This study aims to analyze the criminogenic factors underlying filicide cases in Indonesia through the lens of Robert K. Merton’s Strain Theory. Employing a qualitative method, this research utilizes literature review and content analysis of 33 filicide cases reported by national online media from 2019 to 2025, supported by secondary data from official institutions. The findings indicate that filicide is triggered by various forms of strain stemming from economic hardship, mental disorders, dysfunctional family structures, oppressive cultural norms, and the failure to fulfill the socially constructed ideal parental role. In many cases, perpetrators experienced social isolation and emotional breakdowns due to the cumulative effects of structural and psychological stress. This study concludes that filicide represents a complex form of deviance not merely a consequence of individual psychopathology, but rather a manifestation of systemic social tensions. The study suggests that effective policy interventions should adopt a comprehensive preventive approach, including parenting education, community-based mental health services, and structural reinforcement of family resilience.